Possible role of mammalian secretory group II phospholipase A2 in T-lymphocyte activation: implication in propagation of inflammatory reaction. - Asaoka, Y (1993)
Both 2-lysophosphatidylcholine and cis-unsaturated fatty acids were previously shown to intensify agonist-induced cellular responses by enhancing the diacylglycerol-dependent activation of protein kinase C. Consistent with these observations, extracellular, secretory group II phospholipase A2, when added directly to human resting T lymphocytes, greatly potentiates their activation that was induced by a membrane-permeant diacylglycerol and ionomycin, as determined by the expression of the alpha subunit of the interleukin 2 receptor and thymidine incorporation into DNA. Diacylglycerol and ionomycin were essential for this cellular response, and phospholipase A2 alone showed no effect. The amount of 2-lysophosphatidylcholine produced in these cells by the exogenous phospholipase A2 was greatly increased in the presence of diacylglycerol and ionomycin, suggesting that the membrane phospholipids became susceptible to the phospholipase A2 when protein kinase C was activated. The results suggest that phospholipase A2 secreted into inflammatory sites plays a role in the propagation of cellular responses. Protein kinase C may function in the hydrolysis of membrane phospholipids by the exogenous phospholipase A2, and the products of this phospholipid hydrolysis enhance agonist-induced protein kinase C activation, thereby intensifying cellular responses.